Analisis Kelayakan Usaha(Studi Kasus:Peternakan Ayam Ras Petelur Pak Tarno Di Kelurahan Polokarto, Kecamatan Polokarto, Kabupaten Sukoharjo) - Suprayogi, Maulana (2016)
Analysis of the feasibility of laying chicken farm Tarno pack aim to determine the future prospects of the benefits, advantages and disadvantages in setting up farm laying chicken. In this research needs to be done in the study through the concept of feasibility studies, the aspects analyzed include aspects of the concept feasibility consisting of legal aspects, markets and marketing, technical aspects / operations, management / organization, the economic aspect / social aspects environmental impact analysis and financial aspects. On the legal aspects of business have not been considered adequate because not a corporate official business, but in other aspects of its business may be acceptable or feasible. To determine the feasibility of farm chicken laying the financial aspect is a vital aspect in the feasibility study. Criteria calculations used in determining feasible or not an investment in terms of financial aspects, needs to be measured by several criteria. the criteria used to analyze the feasibility of investment from a business or businesses consist of: (1) The payback period (PP), (2) average rate of return (ARR), net present value (NPV), internal rate of return (IRR), profitability index (PI). Based on the results of the analysis of the test criteria for eligibility of the investment. Based on the results of the analysis of the test criteria for eligibility of these investments indicate where the payback period of the business capital of Rp 250.06 million for 2.029 semester. At the average rate of return method of addressing that level of profits that is 119.0%. Method of net present value (NPV) produces a positive value of Rp 82,544,065. Method of internal rate of return (IRR) generates an interest rate of 31, 139% where the rate of return is greater than the discount rate of 18%. In the method of profitability index (PI) is 1.815, meaning that the value gained more than 1. Based on calculations using the methods explained that the investments carried out by farm chicken laying pack Tarno acceptable or feasible. However, in running the farm chicken laying the need for a reconciliation of the concept of the feasibility study. Repairs should be done on the legal aspects, which do not yet have a business carried on official business entities. Keywords: Analysis, Feasibility, Investment, Ranch Broiler Laying Pak Tarno